Supplementary Material On Partial Fractions: N S S Fs Ds S S S

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Control Theory

KHMak

Supplementary Material on Partial Fractions

Consider the following rational functions


F1 ( s ) = N1 ( s ) s 1 = , D1 ( s ) ( s + 1)( s 2 + 2 s + 2) N 2 (s) s 1 = . D2 ( s ) ( s + 1)( s + 2) 2

F2 ( s ) =

We illustrate the use of two different (but equivalent) methods to obtain their partial fraction decompositions.

Method 1
Typically, for functions like F1(s) which involve complex roots, we write the decomposition as

F1 ( s ) =

s 1 A Bs + C = + 2 . 2 ( s + 1)( s + 2 s + 2) ( s + 1) ( s + 2 s + 2)

This allows us to avoid the manipulation of complex numbers (which can be error-prone). Multiplying both sides with the denominator D1(s) gives
N1 ( s ) = s 1 = A( s 2 + 2 s + 2) + ( Bs + C )( s + 1) . Expanding and collecting powers, we have s 1 = s 2 ( A + B ) + s (2 A + B + C ) + (2 A + C ) . Comparing coefficients gives us 3 simultaneous equations which can be solved for the unknown constants:
A = 2 , B = 2 , C = 3
Note that Method 1 is very general in that it can be used irrespective of the type of roots in the denominator. However, when we have either distinct or repeated first-degree factors, Method 2 is possibly a better choice since it eliminates the need to solve simultaneous equations (of course, there is no reason why they cannot be used in combination)

Control Theory

KHMak

Method 2
F2(s) has one distinct and one repeated first-degree factor, so the decomposition has the form F2 ( s ) = A B C + + . 2 s + 1 ( s + 2) s+2

To find A, we multiply both sides by s + 1 to cancel its denominator: F2 ( s ) ( s + 1) = s 1 B C = A+ ( s + 1) + ( s + 1) . 2 2 ( s + 2) ( s + 2) s+2

Setting s = 1 eliminates the other terms and yields the value of A:

A = F2 ( s ) ( s + 1) |s =1 =

s 1 ( s + 2) 2

= 2 .
s =1

B can be evaluated similarly by B = F2 ( s ) ( s + 2)2 |s =2 = s 1 = 3. ( s + 1) s =2

C presents a problem since s = 2 is a pole of F2 ( s ) ( s + 2) = s 1 A B ( s + 2) + = +C . ( s + 1)( s + 2) ( s + 1) ( s + 2)

To avoid this, we proceed as with B F2 ( s ) ( s + 2) 2 = s 1 A = ( s + 2) 2 + B + C ( s + 2) , ( s + 1) ( s + 1)

but then differentiate once to extract C from the term Cs as well as eliminate B. Setting s = 2 then eliminates the first term and yields C= s 1 d 1 F2 ( s ) ( s + 2) 2 = + =2 2 ds s + 1 ( s + 1) s =2 s =2

In summary, practice and experience will guide you in your choice of method (or combination of methods) to use for partial fraction expansion.
2

You might also like